2016
DOI: 10.3389/fmicb.2016.02093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Lignocellulosic Diets on Bacterial Microbiota and Hydrolytic Enzyme Activities in the Gut of the Cotton Boll Weevil (Anthonomus grandis)

Abstract: Cotton boll weevils, Anthonomus grandis, are omnivorous coleopteran that can feed on diets with different compositions, including recalcitrant lignocellulosic materials. We characterized the changes in the prokaryotic community structure and the hydrolytic activities of A. grandis larvae fed on different lignocellulosic diets. A. grandis larvae were fed on three different artificial diets: cottonseed meal (CM), Napier grass (NG) and corn stover (CS). Total DNA was extracted from the gut samples for amplificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 94 publications
1
12
0
Order By: Relevance
“…Besides genetic structure, host diets, latitude and ecological environment are also quite different. The different food sources can lead to a change in diversity in the microbial community of alimentary canal, thus altering their function and metabolic pathways (Engel and Moran, 2013;Hansen and Moran, 2014; Ben Guerrero et al, 2016;Kelly et al, 2017). The annual diet of L. striatellus in Beijing and Baoding (temperate) consists of wheat and gramineous weeds (Bromus japonicus).…”
Section: Discussionmentioning
confidence: 99%
“…Besides genetic structure, host diets, latitude and ecological environment are also quite different. The different food sources can lead to a change in diversity in the microbial community of alimentary canal, thus altering their function and metabolic pathways (Engel and Moran, 2013;Hansen and Moran, 2014; Ben Guerrero et al, 2016;Kelly et al, 2017). The annual diet of L. striatellus in Beijing and Baoding (temperate) consists of wheat and gramineous weeds (Bromus japonicus).…”
Section: Discussionmentioning
confidence: 99%
“…Cotton boll weevil, as other insects, harbors digestive enzymes with capacity to deconstruct and hydrolyze the plant cell wall (Ben Guerrero et al, 2016). At present, the entire transcriptome of the A. grandis midgut has been sequenced and numerous glycosyl hydrolases enzymes have been identified (Firmino et al, 2013; Salvador et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One of them has been cloned and expressed and its β‐1,4‐endoglucanase activity has been characterized (Ibarra et al, 2019). In addition, the effect of different diets on bacterial gut microbiota and hydrolytic enzyme activities has been characterized in our previous work (Ben Guerrero et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of insect diet on shaping the bacterial microbiota composition was reported in the red palm weevil, Rhynchophorus ferrugineus Olivier, the cotton boll weevil. Anthonomus grandis Boheman, and the pine weevil, Hylobius abietis L. (Montagna et al., ; Ben Guerrero et al., ; Berasategui et al., ). Research by Berasategui et al.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of insect diet on shaping the bacterial microbiota composition was reported in the red palm weevil, Rhynchophorus ferrugineus Olivier, the cotton boll weevil. Anthonomus grandis Boheman, and the pine weevil, Hylobius abietis L. (Montagna et al, 2015;Ben Guerrero et al, 2016;Berasategui et al, 2017). Research by Berasategui et al (2016) on the bacterial community composition in pine weevil populations across Europe revealed that despite significant variation in bacterial community composition, a core bacterial microbiota seemed to be shared by all pine weevil populations.…”
Section: Introductionmentioning
confidence: 99%